2011
DOI: 10.1021/ma200205j
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Morphology of Poly(methyl acrylate)/Silica Nanocomposites

Abstract: Nanoparticles embedded in a polymeric matrix produce polymer "nanocomposites" (PNCs) which can exhibit unique properties. 1,2 The early literature on nylon PNCs provides a good example. Dramatic alteration of the mechanical properties, thermal stability, and gas barrier characteristics result from the addition of relatively small amounts (2À6 wt %) of montmorillonite clay. 3,4 At least some of the property enhancements unique to PNCs are due to alteration of the matrix material near the nanoparticle surface, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…Thus, silica-P2VP mixtures cast from tetrahydrofuran (THF) yield well-dispersed NPs, whereas processing from a pyridine solution results in agglomerated NPs. Durning et al 28 found that silica was well-mixed with poly(methylacrylate), but that the introduction of small quantities of ethyl acetate caused NP agglomeration. Similarly, it is well-known from the work of Mackay et al 12 that the rapid precipitation technique typically yields well-dispersed NP states, regardless of the chemistry of the NPs and the polymers.…”
Section: Kinetics Of Nanoparticle Dispersion and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, silica-P2VP mixtures cast from tetrahydrofuran (THF) yield well-dispersed NPs, whereas processing from a pyridine solution results in agglomerated NPs. Durning et al 28 found that silica was well-mixed with poly(methylacrylate), but that the introduction of small quantities of ethyl acetate caused NP agglomeration. Similarly, it is well-known from the work of Mackay et al 12 that the rapid precipitation technique typically yields well-dispersed NP states, regardless of the chemistry of the NPs and the polymers.…”
Section: Kinetics Of Nanoparticle Dispersion and Assemblymentioning
confidence: 99%
“…While functional groups can be introduced on the polymer chains to aid in this miscibility, a more popular and generalizable strategy is to functionalize the NP with either small ligand molecules or larger polymeric grafts. In addition to aiding in the miscibility of the mixture, 28,32,34,[41][42][43][44][45][46][47][48][49] interestingly, in some instances, the polymer grafting strategy has been shown to convert the NPs into a new class of amphiphiles. This new functionality allows them to self-assemble into a variety of superstructures reflecting their hydrophilic/hydrophobic balance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, polymer–nanoparticle (NP) composites have found applications in many fields due to their enhanced thermomechanical, electrical and mechanical properties . These properties are mainly exhibited in their dispersed state, which is a function of other chemical and physical properties . The properties of the polymer matrix and the processing technology also affect the dispersion of NPs .…”
Section: Introductionmentioning
confidence: 99%
“…1 -5 These properties are mainly exhibited in their dispersed state, which is a function of other chemical and physical properties. 6,7 The properties of the polymer matrix and the processing technology also affect the dispersion of NPs. 8,9 When a polymer − NP composite is prepared by mere physical blending, the strong particle-particle interactions and polymer bridging favour agglomeration due to the high specific area of the NPs, which degrades their useful functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…In general, time and temperature dependent morphologies in filled systems are attributed to the slow diffusion of the embedded particles within the viscous matrix, in a manner that either leads towards improved dispersion or to particle clustering. For example, in poly(methyl acrylate)/silica nanocomposites SAXS data and TEM imaging indicate that particle dispersion is improved following extended thermal treatment (12). In contrast, in PEO/silica nanocomposites, AFM studies reveal the partial flocculation of the filler as a result of thermal annealing (13).…”
Section: Introductionmentioning
confidence: 99%